Metode Role Playing untuk Meningkatkan Kemampuan Dialog Bahasa Jawa pada Siswa Kelas VIII - Suryani; Yuna Irasari Kusuma (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Innovative learning is a challenge for teachers today. Learning does not only convey material but involves students to play an active role during the learning process. This study aims to analyze the role-playing method to improve students' Javanese dialogue skills. This research was conducted at Junior High School 10 Jember with the research subjects is Eighth grade students. This research is classroom action research with quantitative description. Action research stages refer to Kemmis and Taggart, namely the spiral form of the cycle including Planning, Action, Observation, and Reflection. Based on the research, it can be concluded that 1) learning management from cycle I to cycle III has increased to 92.70%. And from the average aspect observed, it obtained a score of 44.5, 2) student activities in the Javanese language learning process, the teacher's activities during learning with an action research model using the role-playing method, 3) students' dialogue ability increased to 92.86% so that the role-playing learning strategy had a positive impact on improving students' dialogue skills.